76.25.14 problem 18

Internal problem ID [17827]
Book : Differential equations. An introduction to modern methods and applications. James Brannan, William E. Boyce. Third edition. Wiley 2015
Section : Chapter 6. Systems of First Order Linear Equations. Section 6.3 (Homogeneous Linear Systems with Constant Coefficients). Problems at page 408
Problem number : 18
Date solved : Tuesday, January 28, 2025 at 11:03:30 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=-5 x_{1} \left (t \right )+x_{2} \left (t \right )-4 x_{3} \left (t \right )-x_{4} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=-3 x_{2} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=x_{1} \left (t \right )-x_{2} \left (t \right )+x_{4} \left (t \right )\\ \frac {d}{d t}x_{4} \left (t \right )&=2 x_{1} \left (t \right )-x_{2} \left (t \right )+2 x_{3} \left (t \right )-2 x_{4} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.162 (sec). Leaf size: 74

dsolve([diff(x__1(t),t)=-5*x__1(t)+1*x__2(t)-4*x__3(t)-1*x__4(t),diff(x__2(t),t)=0*x__1(t)-3*x__2(t)+0*x__3(t)-0*x__4(t),diff(x__3(t),t)=1*x__1(t)-1*x__2(t)-0*x__3(t)+x__4(t),diff(x__4(t),t)=2*x__1(t)-1*x__2(t)+2*x__3(t)-2*x__4(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= -c_{2} {\mathrm e}^{-t}-c_{3} {\mathrm e}^{-2 t}+{\mathrm e}^{-4 t} c_{1} \\ x_{2} \left (t \right ) &= c_4 \,{\mathrm e}^{-3 t} \\ x_{3} \left (t \right ) &= c_{2} {\mathrm e}^{-t}+c_{3} {\mathrm e}^{-2 t} \\ x_{4} \left (t \right ) &= -c_{3} {\mathrm e}^{-2 t}-{\mathrm e}^{-4 t} c_{1} +c_4 \,{\mathrm e}^{-3 t} \\ \end{align*}

Solution by Mathematica

Time used: 0.005 (sec). Leaf size: 168

DSolve[{D[x1[t],t]==-5*x1[t]+1*x2[t]-4*x3[t]-1*x4[t],D[x2[t],t]==0*x1[t]-3*x2[t]+0*x3[t]-0*x4[t],D[x3[t],t]==1*x1[t]-1*x2[t]-0*x3[t]+1*x4[t],D[x4[t],t]==2*x1[t]-1*x2[t]+2*x3[t]-2*x4[t]},{x1[t],x2[t],x3[t],x4[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to e^{-4 t} \left (c_1 \left (e^{2 t}-e^{3 t}+1\right )+\left (e^t-1\right ) \left (c_3 \left (-e^t\right )+(c_2-2 c_3-c_4) e^{2 t}-c_3\right )\right ) \\ \text {x2}(t)\to c_2 e^{-3 t} \\ \text {x3}(t)\to e^{-2 t} \left (c_1 \left (e^t-1\right )-c_2 e^t+2 c_3 e^t+c_4 e^t+c_2-c_3-c_4\right ) \\ \text {x4}(t)\to e^{-4 t} \left (c_1 \left (e^{2 t}-1\right )+c_2 e^t+(-c_2+c_3+c_4) e^{2 t}-c_3\right ) \\ \end{align*}